(untitled) (Journal of Organizational Psychology, 2023)
As employment relationships develop over time, changes in static perceptions of organizational support (POS) provide the basis for evaluating one’s present and future with an organization. We develop and test hypotheses on how POS and referent POS (RΔPOS) trajectories influence employee turnover intentions. Drawing on a sample of 167 employees, our analysis shows that changes to static POS (ΔPOS) and RΔPOS significantly influence employee turnover intentions. This research extends organizational support theory by shedding light on the dynamic nature of POS and the effects of those changes on employee outcomes, specifically turnover intentions.